Implementation of the "Indonesian Jamu Ritual" Concept as a Club Lounge Attraction at the Ritz Carlton Pacific Place - dewi, Maha (Journal of Indonesian Tourism and Policy Studies, 2023)
The purpose of this research is to investigate the implementation of the concept of applying 'Indonesian Jamu Ritual' as a Club Lounge attraction at The Ritz Carlton Pacific Place. The concept is based on the use of traditional Indonesian herbal concoctions that have been used for centuries for health and beauty purposes. The research method used is a qualitative - descriptive approach using data collection techniques through observation, interviews, and documentation. The results showed that the use of the 'Indonesian Jamu Ritual' concept at the Club Lounge The Ritz Carlton Pacific Place can increase hotel guest satisfaction and provide an authentic and unique experience. The implementation of the concept is carried out by providing various types of herbs and traditional Indonesian herbal concoctions. The traditional music presented makes visitors feel like they are in the place where the herbal medicine comes from, which increases the authenticity and atmosphere of consuming herbal medicine. The recommendation from this research is for The Ritz Carlton Pacific Place to continue to improve the implementation of the 'Indonesian Jamu Ritual' concept by adding a variety of herbs and other traditional Indonesian herbal concoctions, as well as improving the quality of service and guest experience by integrating broader elements of Indonesian culture.